You have done right, have confidence in yourself. Just to repeat
f(t)=3t-h(t)= 3t - (4t+2) So f(-1) = 3(-1) - ( -4 + 2 ) = -3 + 2 = -1
g(n)=n^3+2n^2−7n+5+f(n)
So g(f(-1))=g(-1) = (-1)^3+2(-1)^2−7(-1)+5+f(-1)
= -1 +2+7+5-1 = 12
Hi All,
I am teaching my self algebra using khan academy and Ive come across a problem I cant figure out. I am trying to solve composite functions and I cant figure out why a Plus sign is added to the equation, Could I be missing something that I am suppose to distrubute?
The functions is:
g(f(−1))=?
h(x)=4x+2
g(n)=n^3+2n^2−7n+5+f(n)
f(t)=3t−h(t)
f(−1)=−1
g(−1)=(−1)^3+2(−1)^2 + (−7)(−1)+5+f(−1)
where does this............Δ Plus sign come from?
You have done right, have confidence in yourself. Just to repeat
f(t)=3t-h(t)= 3t - (4t+2) So f(-1) = 3(-1) - ( -4 + 2 ) = -3 + 2 = -1
g(n)=n^3+2n^2−7n+5+f(n)
So g(f(-1))=g(-1) = (-1)^3+2(-1)^2−7(-1)+5+f(-1)
= -1 +2+7+5-1 = 12